Outcomes in terms of Mortality in patients of Community Acquired Pneumonia with Raised B-Type Natriuretic Peptide - Amna Mansoor; Binish Hayat; Afshan Noureen Arain; Shumail Arslan; Hafsa Mansoor; Zeeshan Talib (Indus Journal of Bioscience Research, 2025)
Background: Community-acquired pneumonia (CAP) remains a leading cause of morbidity and mortality worldwide. While B-type natriuretic peptide (BNP) is primarily recognized as a cardiac stress biomarker, emerging evidence suggests its elevation in non-cardiac conditions contribute to myocardial strain. Aim: To evaluate the outcomes in terms of mortality and clinical progression among patients with CAP exhibiting elevated BNP levels, and to assess the association of BNP with inflammatory markers, oxygen requirement, and other clinical endpoints. Methodology: A prospective, comparative study was conducted involving 60 patients diagnosed with CAP and 60 age- and sex-matched healthy controls. BNP, C-reactive protein (CRP), white blood cell count (WBC), and erythrocyte sedimentation rate (ESR) were measured in both groups. In CAP patients, BNP levels were assessed at admission and post-treatment. Clinical data including symptom duration, hospital stay, FiO₂ requirement, PaO₂, and outcomes such as mortality, ICU admission, and mechanical ventilation were recorded. Statistical analyses included t-tests, correlation coefficients, and p-value assessments for group comparisons and prognostic associations. Results: CAP patients demonstrated significantly elevated BNP at admission (84.56 ± 22.58 pg/ml) compared to controls (31.50 ± 7.12 pg/ml, p < 0.0001), with post-treatment reduction to 41.06 ± 9.58 pg/ml (p < 0.001). BNP was significantly correlated with FiO₂ requirement (r = 0.313, p = 0.0149) and mechanical ventilation (r = 0.256, p = 0.0479), while weak positive correlations with mortality and ICU admission did not reach statistical significance. Mortality occurred in 3.3% of cases, exclusively within the high BNP (>100 pg/ml) subgroup. Patients with BNP ≤47 pg/ml had an uncomplicated clinical course without adverse outcomes. Inflammatory markers (CRP, WBC, ESR) were also significantly higher in CAP patients compared to controls (p < 0.0001). Conclusion: Elevated BNP levels in CAP patients are strongly associated with respiratory severity and clinical deterioration, particularly oxygen dependency and risk of mechanical ventilation. While not an independent predictor of mortality in this sample size, BNP provides meaningful stratification of clinical risk, with low values reliably indicating favorable outcomes. BNP measurement may thus serve as a valuable adjunct for early prognostication and management decisions in CAP.